Correlation of Electrical Properties and Acoustic Loss in Single Crystalline Lithium Niobate-Tantalate Solid Solutions at Elevated Temperatures - Yuriy Suhak (Crystals, 2021)
Electrical conductivity and acoustic loss Q−1 of single crystalline Li(Nb,Ta)O3 solid solutions (LNT) are studied as a function of temperature by means of impedance spectroscopy and resonant piezoelectric spectroscopy, respectively. For this purpose, bulk acoustic wave resonators with two different Nb/Ta ratios are investigated. The obtained results are compared to those previously reported for congruent LiNbO3. The temperature dependent electrical conductivity of LNT and LiNbO3 show similar behavior in air at high temperatures from 400 to 700 °C. Therefore, it is concluded that the dominant transport mechanism in LNT is the same as in LN, which is the Li transport via Li vacancies. Further, it is shown that losses in LNT strongly increase above about 500 °C, which is interpreted to originate from conductivity-related relaxation mechanism. Finally, it is shown that LNT bulk acoustic resonators exhibit significantly lower loss, comparing to that of LiNbO3.